PENGARUH COMPACT DISK(CD) MULTIMEDIA INTERAKTIF DALAM MODEL PROBLEM BASED LEARNING BERBANTUAN LKPD TERHADAP CRITICAL THINKING SKILL PESERTA DIDIK KELAS X SMAN 1 PADANG - Cici Lestari; Djusmaini Djamas; Murtiani Murtiani (Universitas Negeri Padang, 2017)
Critical thinking skills are still not optimal shows learners is still difficult to understand the concepts and principles of physics. One possible cause is the use of media that do not support learners to develop critical thinking skills. Interactive multimedia CD in problem based learning models aided LKPD is expected to be effective ways to improve the critical thinking skills of learners. The purpose of this study was to investigate the influence of interactive multimedia CD in problem based learning models aided LKPD the critical thinking skills of students grade X SMAN 1 Padang. This research is a quasi-experimental study with a randomized control group design ppretest- posttest design. The population in this study were all grade X SMAN 1 Padang MIA Academic Year 2016/2017. Sampling was done in two stages, using purposive sampling to determine the grade educators to be used and cluster random sampling to determine the appropriate sample class. The instrument used in this study is in the form of a written test about the description. Data obtained from the critical thinking skills score is performed on the answers of students who identifies indicators of critical thinking skills. Data were analyzed with the equality test two averages using statistical t test and regression and correlation to determine the relationship between independent variables and variable control. The test results showed thitungtcount of 2.57 is outside the reception area of Ho. This shows the significant difference from the average value of critical thinking skills between the two classes of samples. Product Moment Correlation analysis showed 31.40% critical thinking skills are affected by the implementation of interactive multimedia CD in problem based learning models aided LKPD and the remaining 68.6% is influenced by other factors. Thus, it can be concluded that there is a significant impact on the use of interactive multimedia CD in problem based learning models aided LKPD against citical thinking skills of students in the 5% significance level